2008
DOI: 10.1038/ijo.2008.63
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index at various ages and mortality in Chinese women: impact of potential methodological biases

Abstract: Background: Inadequate control for potential methodological biases has been suggested as an explanation for the conflicting findings concerning the relationship between body mass index (BMI) and mortality. Methods: Using data from the Shanghai Women's Health Study, a prospective cohort study conducted in a relatively lean population, we examined the associations of BMI at various ages and average adult BMI with mortality and evaluated the impact of potential biases related to preexisting illness and cigarette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
(43 reference statements)
1
15
1
1
Order By: Relevance
“…Our study even suggested a lower risk of mortality among underweight individuals. This contrasts to findings from previous studies that showed an increased risk of total mortality among underweight individuals (2, 3, 5, 10, 11) but is similar to findings in the Nurses’ Health Study (6) and few other studies of Asians (18, 19). While the relation of underweight to mortality and the underlying reasons for this relation are areas of ongoing research, studies have shown that the association is largely due to excess deaths from respiratory and infectious diseases and likely reflects at least in part weight loss due to underlying chronic diseases (5, 11).…”
Section: Discussioncontrasting
confidence: 55%
“…Our study even suggested a lower risk of mortality among underweight individuals. This contrasts to findings from previous studies that showed an increased risk of total mortality among underweight individuals (2, 3, 5, 10, 11) but is similar to findings in the Nurses’ Health Study (6) and few other studies of Asians (18, 19). While the relation of underweight to mortality and the underlying reasons for this relation are areas of ongoing research, studies have shown that the association is largely due to excess deaths from respiratory and infectious diseases and likely reflects at least in part weight loss due to underlying chronic diseases (5, 11).…”
Section: Discussioncontrasting
confidence: 55%
“…To address these problems, investigators in multiple studies have performed analyses using data from nonsmokers only and from people who reported no serious underlying illness at the time of enrollment or have excluded from the analyses the early years of follow-up. 13-16 However, in our study, the PSC project, and the KCPS, as well as in some other large cohort studies, 6-10 a J-shaped or U-shaped relation between BMI and the risk of death persisted after major methodologic issues were addressed.…”
Section: Discussionmentioning
confidence: 45%
“…Though many studies have shown an increased risk of all cause mortality with greater adiposity as measured by body mass index (BMI), 15 16 17 18 19 20 21 22 23 24 questions remain about the shape of the dose-response relation. Several large scale prospective studies 15 16 17 18 19 20 21 22 23 24 and pooled analyses (each with 900 000 to 1.46 million participants) 2 14 25 have reported increased risk of all cause mortality with greater BMI, and most of these found the lowest risk among participants with BMI in the range of 20 or 22.5 to 24.9. A large meta-analysis of 97 cohort studies with 2.88 million participants and 270 000 deaths, which used the WHO cut-off points for overweight and obesity, however, found summary hazard ratios of 0.94 (95% confidence interval 0.90 to 0.97), 0.97 (0.90 to 1.04), and 1.34 (1.21 to 1.47) for a BMI of 25-<30, 30-<35, and ≥35, respectively, suggesting a protective effect of overweight on mortality and that only severely obese people are at increased risk of mortality.…”
Section: Introductionmentioning
confidence: 99%